Etnoconhecimento nos quintais urbanos em mossoró/rn - Moura, Ana Paula de (2019)
Urban backyards are of great historical and socio-cultural importance, since plant species grown in urban areas improve environmental quality, bring aesthetic benefits, serve for the production of food and medicinal plants, among other purposes. In fact, research in the area of ethnobotany in urban areas is still incipient, especially in the semi-arid region, in terms of environmental impacts, food, people's health and even income generation. Therefore, this work aims to carry out an ethnobotanical survey in the urban backyards of Conjunto Vingt Rosado, in Bairro Rincão, in Mossoró / RN. The methodological procedures consisted of: Application of a semi-structured questionnaire, built with objective and open questions; Identification of plant species present in urban backyards and gardens, listed in a specific worksheet. In all houses, about 100 houses, there are plant cultivations. Eighteen plant ethnospecies were found, for different purposes, according to the residents themselves, with emphasis on the species for consumption of fruits, seeds, leaves or processed; plants for medicinal purposes; besides species for ornamental use and shading. The motivations for planting are quite varied and it takes into account, from aesthetic, cultural and shading aspects, to the production of food and cultivation of plants considered medicinal. In the latter case, it was found that knowledge is almost always associated with information passed on by older family members or common sense ethnoculture. Thus, it is concluded that the gardens and backyards of the Vingt Rosado complex have a great potential for botanical cultivation and the expansion of this possibility can bring quite a lot of benefits from the point of view of food and environmental security and even expand the possibilities of generation. local income. Actions aimed at environmental education and home economics can be very useful, to expand these possibilities of propagation and use of plants. One of the most relevantaspects of plant cultivation is the transfer of ethnobotanical knowledge. Without the involvement of younger people, such knowledge can be quickly lost or considered obsolete, due to the ease of finding food in markets and medicinal plants, increasing people'sdependence on agro-industrialized products and the strong pharmaceutical industry.